Responses of the squash bug (Hemiptera: Coreidae) and its egg parasitoid, Gryon pennsylvanicum (Hymenoptera: Scelionidae) to three Cucurbita cultivars - Vogt, Elizabeth A.; Nechols, James R. (My University, 2013)
Laboratory experiments were conducted to quantify effects of resistant and susceptible host plants on the preimaginal and adult biologies of the squash bug, Anasa tristis (De Geer), and its egg parasitoid, Gryon pennsylvanicum (Ashmead). `Early Prolific Straightneck' squash, `Green Striped Cushaw' pumpkin, and `Waltham Butternut' squash served as test plants. Preimaginal development of the squash bug (egg to adult) was similar on all three cultivars (range: 31-35 d). However, survivorship to the adult was significantly lower on `Green Striped Cushaw' and `Waltham Butternut' than on `Early Prolific Straightneck'. Statistical differences in survivorship were not observed in second-generation squash bugs, suggesting that some selection may have occurred. Squash bug reproduction and longevity were similar on all three cultivars. However, the reduced juvenile survivorship on `Green Striped Cushaw' and `Waltham Butternut' resulted in significantly lower r[subscript max] values on these cultivars than on the more susceptible `Early Prolific Straightneck'. The dietary history of adult squash bugs did not significantly affect development, preimaginal survival, or reproduction of G. pennsylvanicum. However, adult longevity of the parasitoid was significantly reduced when its larvae developed in eggs of squash bugs that were reared on the most resistant cultivar (`Waltham Butternut').
Citation: Vogt, A, and James R Nechols. 1993. “Responses of the Squash Bug (Hemiptera: Coreidae) and Its Egg Parasitoid, Cryon Pennsylvanicum (Hymenoptera: Scelionidae) to Three Cucurbita Cultivars.” ENVIRONMENTAL ENTOMOLOGY 22 (1): 8.
Keywords: Tri-trophic interactions; Biological control; Host plant resistance; Squash bug; Gryon pennsylvanicum